2001
DOI: 10.1023/a:1013663126973
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Experiments on rats trained passive avoidance task showed that N-phenyl-acetyl-L-prolyl-glycyl ethyl ester, peptide analog of piracetam (GVS-111, Noopept) after oral administration retained antiamnesic activity previously observed after its parenteral administration. Effective doses were 0.5-10 mg/kg. Experiments on a specially-developed model of active avoidance (massive one-session learning schedule) showed that GVS-111 stimulated one-session learning after single administration, while after repeated adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The blockade of spectral changes by the NMDA antagonist revealed in our study suggests that this type of glutamate receptors can be involved in the mechanisms of the EEG effects of both piracetam and GVS-111. This suggestion is supported by the data on noncompetitive effects of piracetam on 3H-piracetam binding to rat brain membranes in vitro [8], GVS-111-induced alleviation of amnesia caused by MK-801, a noncompetitive antagonist of NMDA receptors [9], CPP-induced reversal of the effect of GVS-111 on the release of dopamine from rat striatum in vitro [10].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The blockade of spectral changes by the NMDA antagonist revealed in our study suggests that this type of glutamate receptors can be involved in the mechanisms of the EEG effects of both piracetam and GVS-111. This suggestion is supported by the data on noncompetitive effects of piracetam on 3H-piracetam binding to rat brain membranes in vitro [8], GVS-111-induced alleviation of amnesia caused by MK-801, a noncompetitive antagonist of NMDA receptors [9], CPP-induced reversal of the effect of GVS-111 on the release of dopamine from rat striatum in vitro [10].…”
Section: Resultsmentioning
confidence: 72%
“…Proceeding from the original concept on the peptidergic nature of the nootropic effects of piracetam [4], GVS-111 dipeptide (N-phenylacetyl-L-prolylglycine ethyl ester) was synthesized and pharmacologically tested .in the Institute of Pharmacology, Russian Academy of Medical Sciences [7,9]. The mnemotropic activity of GWS-111 2-4 thousand times surpassed that of piracetam.…”
mentioning
confidence: 99%
“…Following the isolation of cGP from rat brain tissue [ 37 ], the neurological function of cGP and its analogues have been extensively examined by different researchers. Gudasheva et al reported the efficacy of cGP and its analogues in protecting the brain from ischemic brain injuries and improving cognitive function [ 38 , 39 , 40 ]. Experimental research shows that both GPE and cGP exhibit pharmacological effects similar to those of IGF-1.…”
Section: Cgp Is a Bioactive Compoundmentioning
confidence: 99%